Prevalence of obesity, diabetes and hypertension in immigrant populations in northeastern Mexico - Gómez-Morales, Guillermo Baudelio; Rosas-Torres, Brenda Sofía; Hernández-Jiménez, Williams Jesús; Mattenberger-Cantú, Estefanía; Vargas-Villarreal, Javier; Almanza-Reyes, Horacio; González-Salazar, Francisco (Frontiers in Public Health, 2024)
Introduction: Hispanic immigrants are a fast-growing population in the United States of America (USA) that suffer disproportionately from chronic diseases. Despite the increasing prevalence of obesity in Latin American countries, only few studies have examined the onset of chronic diseases in Mexican and Central American migrants in Mexico.Objective: Determine the prevalence of obesity, diabetes, and hypertension in Central American immigrants who are in the process of traveling through northeastern Mexico to the USA.Methods: An observational and, descriptive, cross-sectional study was conducted among migrants, mostly Central Americans. Migrants who agreed to participate in the study were interviewed face-to-face by researchers to obtain their sociodemographic data. To obtain the prevalence, many health indicators related to obesity, diabetes and hypertension were measured, including weight, height, fasting glucose, and blood pressure.Results: 520 migrants were interviewed; sociodemographic data indicated that most participants were male (76%), from Honduras (72.6%), single (61.2%), and with elementary education (48.6%). On the somatometric evaluation, it was reported that 28.9% were diagnosed as overweight, 10.7% with obesity and 3.3% with malnutrition. Of less prevalence, 8.8% were detected with hypertension, and 4.6% had fasting hyperglycemia. The mean participant age was 29.11 years ± 10.00. The average participant weight was 66.72 kg ± 13.09 and the average height was 1.64 m ± 0.08. The average body mass index This is a provisional file, not the final typeset article (BMI) was 24.59 ± 4.32. The mean systolic and diastolic pressure were 116.26 ± 15.13 and 74 ± 9.65, respectively. People from Mexico, Nicaragua and Honduras reported a high prevalence of overweight (63.6, 47.4 and 30.7% respectively), while people from El Salvador and Nicaragua had a high prevalence in obesity (23.5 and 21.1%, respectively). We found significant differences in the rates of obesity, diabetes, and hypertension between groups of Central American migrants and their place of origin, age, educational level, and gender. Our findings underscore the importance of exploring differences within groups of Central American migrants traveling through northeastern Mexico to the USA that may explain several health indicators.